2022
DOI: 10.1371/journal.pntd.0010415
|View full text |Cite
|
Sign up to set email alerts
|

Malaria transmission structure in the Peruvian Amazon through antibody signatures to Plasmodium vivax

Abstract: Background The landscape of malaria transmission in the Peruvian Amazon is temporally and spatially heterogeneous, presenting different micro-geographies with particular epidemiologies. Most cases are asymptomatic and escape routine malaria surveillance based on light microscopy (LM). Following the implementation of control programs in this region, new approaches to stratify transmission and direct efforts at an individual and community level are needed. Antibody responses to serological exposure markers (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…First, as a cross-sectional, this study is not designed to infer malaria transmission intensity. In this case, the seroprevalence reflects recent exposure to malaria infection (up to 9 months in the past) 31,33 , however no active infection data was used. Despite other studies demonstrating that malaria seroprevalence is a good proxy for malaria transmission intensity 11,60,61 , further longitudinal studies, to deal with potential regressions to the mean issues, are suggested to determine the causal effect on malaria transmission intensity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, as a cross-sectional, this study is not designed to infer malaria transmission intensity. In this case, the seroprevalence reflects recent exposure to malaria infection (up to 9 months in the past) 31,33 , however no active infection data was used. Despite other studies demonstrating that malaria seroprevalence is a good proxy for malaria transmission intensity 11,60,61 , further longitudinal studies, to deal with potential regressions to the mean issues, are suggested to determine the causal effect on malaria transmission intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Seropositivity to each marker was defined by using a Random Forests based classification algorithm previously validated in low P. vivax transmission contexts 33 . Further description of the serological makers and the measured structure of the transmission in the area could be found elsewhere 31 .…”
Section: Data Collection and Variable Definitions A Full Census Of Th...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although SNA and connectivity metrics yield no significant differences, geographic-specific characteristics must be considered when assessing their effect on malaria transmission(21,23). We found high heterogeneity in malaria transmission in the Loreto region at the micro-geographical level, with nearby communities having different transmission scenarios (20,21,23,37). Malaria transmission in the Mazan district is more intense than in the Iquitos district [Mean API 2019-2020: 37.93 and 2.95, respectively] (22).…”
Section: Discussionmentioning
confidence: 86%